Does the Choice of the Multivariate GARCH Model on Volatility Spillovers Matter? Evidence from Oil Prices and Stock Markets in G7 Countries - Kartsonakis-Mademlis, Dimitrios; Dritsakis, Nikolaos (International Journal of Energy Economics and Policy, 2020)
In this paper, we employ asymmetric multivariate GARCH approaches to examine their performance on the volatility interactions between global crude oil prices and seven major stock market indices. Insofar as volatility spillover across these markets is a crucial element for portfolio diversification and risk management, we also examine the optimal weights and hedge ratios for oil-stock portfolio holdings with respect to the results. Our findings highlight the superiority of the asymmetric BEKK model and the fact that the choice of the model is of crucial importance given the conflicting results we got. Finally, our results imply that oil assets should be a part of a diversified portfolio of stocks as they increase the risk-adjusted performance of the hedged portfolio. Keywords: Asymmetry, Multivariate GARCH, Stock market, Oil price, Volatility Spillover JEL Classifications: C32, F3, G15, Q4 DOI: https://doi.org/10.32479/ijeep.9469